Somali Refugee Solutions in Kenya: Challenges of Repatriation and Prospects of Local Integration. - Peter, Kirui; Wanyonyi, Hellen S.; Kutto, Naomi (Advances in Social Sciences Research Journal, 2020)
This paper assesses the challenges of voluntary repatriation of Somali refugees in Kenya and the prospects of local integration, if considered. It aims to demonstrate that no one refugee solution is adequate and that all available options ought to be pursued concurrently for optimum results. Based on review of existing literature, the paper traces the trajectory of Somali refugees in Kenya amidst a continually restrictive space for refugees among host states like Kenya.While the tripartite agreement on voluntary repatriation has seen many Somali refugees voluntarilly repatriate, many challenges abound and a majority yet to repatriate.This therefore calls for an assessment of other refugee solution options, like local integration.It concludes that repatriation, resettlement and local integration, all provide options for a comprehensive Somali refugee solution in Kenya.